An electromyographic study of trunk muscles in open stance and closed stance tennis two-handed backhands - Gomez-Cuesta, S.; Nowicky, A. (Medicine and Science in Tennis, 2004)
The purpose of this study was to compare the external oblique and erector spinae muscle activation in the open stance and closed stance tennis two-handed backhands, with the aim to provide objective evidence of the hypothesis of the reliance on greater trunk muscle contribution in the open stance two-handed backhand compared to the closed stance two-handed backhand.